2005
DOI: 10.1158/0008-5472.can-05-1042
|View full text |Cite
|
Sign up to set email alerts
|

Perifosine Inhibits Multiple Signaling Pathways in Glial Progenitors and Cooperates With Temozolomide to Arrest Cell Proliferation in Gliomas In vivo

Abstract: Perifosine is an oral Akt inhibitor which exerts a marked cytotoxic effect on human tumor cell lines, and is currently being tested in several phase II trials for treatment of major human cancers. However, the efficacy of perifosine in human gliomas has not been established. As Akt is activated in f70% of human glioblastomas, we investigated the impact of perifosine on glia in culture and on a mouse glioma model in vivo. Here we show that perifosine strongly reduces phosphorylation levels of Akt and extracellu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 172 publications
(112 citation statements)
references
References 25 publications
7
104
0
1
Order By: Relevance
“…U0126 specifically inhibited phosphorylation of Erk1/2 to the basal levels, although having no effect on phospho-Akt and its downstream targets (Figure 1c), whereas LY294002 slightly reduced Akt, mTOR and S6 ribosomal protein phosphorylation to a similar extent as rapamycin. Treatment with perifosine caused a significant inhibition of both Akt and S6 ribosomal protein after 2 h of treatment, whereas having less effect on ERK1/2, consistent with previous studies (Momota et al, 2005). The largest increase in La levels was observed on PDGFB treatment and was completely reversed to the basal level by perifosine and LY294002 treatment; U0126 treatment had a lesser effect and rapamycin treatment did not affect the level of La protein.…”
Section: External Growth Stimuli Regulate La Protein Levels Through Asupporting
confidence: 90%
“…U0126 specifically inhibited phosphorylation of Erk1/2 to the basal levels, although having no effect on phospho-Akt and its downstream targets (Figure 1c), whereas LY294002 slightly reduced Akt, mTOR and S6 ribosomal protein phosphorylation to a similar extent as rapamycin. Treatment with perifosine caused a significant inhibition of both Akt and S6 ribosomal protein after 2 h of treatment, whereas having less effect on ERK1/2, consistent with previous studies (Momota et al, 2005). The largest increase in La levels was observed on PDGFB treatment and was completely reversed to the basal level by perifosine and LY294002 treatment; U0126 treatment had a lesser effect and rapamycin treatment did not affect the level of La protein.…”
Section: External Growth Stimuli Regulate La Protein Levels Through Asupporting
confidence: 90%
“…2), we suggest that JNK activation is unlikely to account for the perifosine-induced apoptosis in human NSCLC cells. Perifosine was reported to either decrease or increase ERK phosphorylation depending on cancer cell type (5,18,27). In our study, perifosine decreased ERK phosphorylation in all of the three tested cell lines tested, regardless of cell sensitivity to TRAILinduced apoptosis.…”
Section: Discussionsupporting
confidence: 47%
“…Modulation of Akt, JNK, and ERK signaling pathways and their involvement in perifosine-induced apoptosis has been studied in other types of cancer cells (4,18,27). Despite the proapoptotic role of JNK activation in perifosine-induced apoptosis in multiple myeloma (18), we found that perifosine increased p-c-Jun only in one (i.e., H157 cells) of three cell lines tested (Fig.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…16,17 In addition to inhibition of PI3K-Akt signaling, in some cell types perifosine downregulates the antiapoptotic mitogenactivated protein kinase-extracellular signal-regulated kinase (MEK-ERK) 1/2 pathway and activates the proapoptotic c-jun-Nkinase (JNK) network, thus modulating the balance between the survival and death signaling cascades, thereby inducing apoptosis. 16,18 At present, perifosine is the most developed Akt inhibitor from a clinical point of view. 19 The PI3K-Akt pathway is activated in most acute myelogenous leukemia (AML) cases, where it markedly influences survival and chemosensitivity.…”
Section: Introductionmentioning
confidence: 99%